An Integration of Family and School on Strengthening the Character of Teenager in Indonesia: It’s a Must - Alfiasari Alfiasari; Dwi Hastuti; Sarwititi Sarwoprasodjo (Department of Family and Consumer Sciences, Bogor Agricultural University, 2016)
Juvenile delinquencies that have increased in the last few years among teenagers in Indonesia need some integrative efforts to overcome. This study analysed influence of parenting styles, methods of socialization, and school environment on character strengths among teenagers. This study also examined what family and school can do to improve their character strengths. This study involved 400 students conducted in 10 senior high schools in rural and urban area in Bogor, West Java Province, Indonesia. The result of this study revealed that some factors in the family (low level of permissive parenting style, high level of authoritative parenting style, higher variations of methods of socialization) and school environment (low of punishment and low violent behavior received in school, higher preference for learning process and condition at school) had significant and positive influence to increase quality of character. Hence, integration of partnership between family and school to strengthen teenagers’ character is discussed further in this study. Keywords: character strengths, methods of socialization, parenting style, school environment Kenakalan remaja yang telah meningkat dalam beberapa tahun terakhqir di kalangan remaja di Indonesia memerlukan upaya integratif. Penelitian ini menganalisis pengaruh gaya pengasuhan, metode sosialisasi, dan lingkungan sekolah pada kekuatan karakter di kalangan remaja. Penelitian ini juga meneliti hal yang dapat dilakukan keluarga dan sekolah untuk meningkatkan kekuatan karakter remaja. Penelitian ini melibatkan 400 siswa yang dilakukan di 10 SMA di daerah pedesaan dan perkotaan di Bogor, Provinsi Jawa Barat, Indonesia. Hasil penelitian ini menunjukkan bahwa beberapa faktor dalam keluarga (gaya pengasuhan permisif tingkat rendah, gaya pengasuhan otoritatif tingkat tinggi, metode sosialisasi dengan variasi yang tinggi) dan lingkungan sekolah (tingkat hukuman yang rendah dan perilaku kekerasan yang rendah diterima di sekolah, preferensi yang lebih tinggi untuk proses belajar dan kondisi di sekolah) memiliki pengaruh yang positif signifikan untuk meningkatkan kualitas karakter. Oleh karena itu, integrasi kemitraan antara keluarga dan sekolah untuk memperkuat karakter remaja dibahas lebih lanjut dalam penelitian ini.Kata kunci: gaya pengasuhan, kekuatan karakter, lingkungan sekolah, metode sosialisasi